Nightclub city : politics and amusement in Manhattan - Peretti, Burton W. (Burton William), 1961- (University of Pennsylvania Press, 2007)
This dark and dazzling history of New York City nightclub life in the 1920s and '30s explores the complex relationships among urban politicians, social reformers, and the business of vice.